2016
DOI: 10.5217/ir.2016.14.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of endoscopic resection using the band ligation method for rectal neuroendocrine tumors

Abstract: Background/AimsRectal neuroendocrine tumors (NETs) are among the most common of gastrointestinal NETs. Due to recent advances in endoscopy, various methods of complete endoscopic resection have been introduced for small (≤10 mm) rectal NETs. However, there is a debate about the optimal treatment for rectal NETs. In our study, we aimed to evaluate the efficacy and feasibility of endoscopic resection using pneumoband and elastic band (ER-BL) for rectal NETs smaller than 10 mm in diameter.MethodsA total of 55 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…EMR-L requires less technical skill, and snare resection below the band ligation is effective in achieving a negative vertical margin. Earlier evaluations have attested to the acceptable safety and outcomes of EMR-L treatment for rectal NET (8-10). The procedure can be performed safely within a short period of time and allows for a relatively precise histological assessment of the resected margin (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…EMR-L requires less technical skill, and snare resection below the band ligation is effective in achieving a negative vertical margin. Earlier evaluations have attested to the acceptable safety and outcomes of EMR-L treatment for rectal NET (8-10). The procedure can be performed safely within a short period of time and allows for a relatively precise histological assessment of the resected margin (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important reasons for the superior outcomes of ESMR‐L is its low VM positive rate. Previous reports revealed that the VM positive rate was 22.6–50% in cEMR, 23 , 25 , 26 , 27 , 28 0–29.2% in ESD, 13 , 23 , 25 , 29 and 0–10% in ESMR‐L. 13 , 23 , 25 , 26 , 28 , 29 …”
Section: Discussionmentioning
confidence: 94%
“…Previous reports revealed that the VM positive rate was 22.6–50% in cEMR, 23 , 25 , 26 , 27 , 28 0–29.2% in ESD, 13 , 23 , 25 , 29 and 0–10% in ESMR‐L. 13 , 23 , 25 , 26 , 28 , 29 …”
Section: Discussionmentioning
confidence: 94%
“…In recent times, studies have reported the efficacy of m-EMR in the treatment of rectal neuroendocrine tumors [16][17][18][19][20][21][22][23][24][25][26]. However, the efficacy and safety of m-EMR versus EMR needs further evaluation.…”
Section: Introductionmentioning
confidence: 99%